Participation in continuous, on-the-job training and the impact on job satisfaction: longitudinal evidence from the German labour market - Georgellis, Y.; Lange, Thomas (Routledge, 2007)
A number of studies in the human resources literature acknowledge the importance of workplace training for inducing organizational commitment on the part of workers. However, small sample sizes and the absence of relevant panel data have raised concerns about the general validity of results and highlighted the need for further research to explicitly include on-the-job training as an important facet of job satisfaction. A similar empirical gap exists in the economics and industrial organization literature, where, despite the importance of both on-the-job training and job satisfaction to influence labour productivity, the relationship between the two has received surprisingly little attention. The aim of this paper is to bridge this gap in our knowledge and assess the impact of further training on job satisfaction in the western regions of Germany. We use data derived from the German Socio-economic Panel, which covers the period 1984 to 2002. Concentrating on full-time employed individuals, we focus in particular on the 1989, 1993 and 2000 interview waves, which include a number of questions on work-related training and offer detailed information on the type and duration of training received, and whether employers sponsored such training. The empirical results of the study provide information about the decision to participate in further training and the latter's impact on job satisfaction. Gender inequality issues in Germany's segmented labour market are explained by reference to discrepancy theory, equity theory, social exchange theory and the perception of a breach in the psychological contract between firms and female trainees.